2016
DOI: 10.18203/2320-6012.ijrms20164186
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal outcomes in HIV positive pregnant female

Abstract: Mother to child transmission (MTCT) is not an uncommon mode of HIV transmission, especially in resource poor countries. The transmission of HIV from HIV-positive mother to her child during pregnancy, labour, delivery or breastfeeding is called mother-to-child transmission. According to current NACO guidelines pregnant women who are found HIV positive, should have immediate and lifelong ART to treat HIV and improve her own health, maximally suppress maternal viral load prior to conception to decrease the risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Neonates with IUGR were associated with iatrogenic preterm birth and needed a longer NICU stay [3][4][5]. Mittal et al reported that in a group of patients who received longer cART, the incidence of IUGR was 27%, which was associated with apoptosis-related placental insufficiency [6].…”
Section: Review Of Apoptosismentioning
confidence: 99%
“…Neonates with IUGR were associated with iatrogenic preterm birth and needed a longer NICU stay [3][4][5]. Mittal et al reported that in a group of patients who received longer cART, the incidence of IUGR was 27%, which was associated with apoptosis-related placental insufficiency [6].…”
Section: Review Of Apoptosismentioning
confidence: 99%